Biocultural Strategies for Measuring Psychosocial Stress Outcomes in Field-based Research. Issue 4 (November 2021) - Brewis, Alexandra; Piperata, Barbara A.; Dengah, H. J. François; Dressler, William W.; Liebert, Melissa A.; Mattison, Siobhán M.; Negrón, Rosalyn; Nelson, Robin; Oths, Kathryn S.; Snodgrass, Jeffrey G.; Tanner, Susan; Thayer, Zaneta; et al.
The goal of assessing psychosocial stress as a process and outcome in naturalistic (i.e., field) settings is applicable across the social, biological, and health sciences. Meaningful measurement of biology-in-context is, however, far from simple or straightforward. In this brief methods review, we introduce theoretical framings, methodological conventions, and ethical concerns around field-collection of markers of psychosocial stress that have emerged from 50 years of research at the intersection of anthropology and human biology. Highlighting measures of psychosocial stress outcomes most often used in biocultural studies, we identify the circumstances under which varied measures are most appropriately applied and provide examples of the types of cutting-edge research questions these measures can address. We explain that field-based psychosocial stress measures embedded in different body systems are neither equivalent nor interchangeable, but this recognition strengthens the study of stress as always simultaneously cultural and biological, situated in local ecologies, social–political structures, and time.